Real-Life Experience of mTOR Inhibitors in Liver Transplant Recipients in a Region Where Living Donation Is Predominant - Sung, Pil Soo; Han, Ji Won; Seo, Changho; Ahn, Joseph; Lee, Soon Kyu; Nam, Hee Chul; Choi, Ho Joong; You, Young Kyoung; Jang, Jeong Won; Choi, Jong Young; Yoon, Seung Kew (Frontiers in Pharmacology, 2021)
Background: Mammalian target of rapamycin (mTOR) inhibitors, such as everolimus and sirolimus, may be efficacious in preserving renal function in liver transplantation (LT) recipients while preventing hepatocellular carcinoma (HCC) recurrence. Materials and Methods: In this study, we retrospectively evaluated the safety, efficacy, and renoprotective effects of mTOR inhibitors in LT recipients. Among the 84 patients enrolled, mTOR inhibitor was commenced during the first year after LT. Renal function was measured by estimated glomerular filtration rate (eGFR) using the Modification of Diet in Renal Disease equation. Results: Regarding the type of mTOR inhibitor, everolimus was used in 71 patients and sirolimus in 13 patients. Concomitant tacrolimus was used in 63 patients (75.0 %). For total enrolled patients, kidney function did not significantly change during 12 months after initiation of mTOR inhibitors, although tacrolimus-withdrawn patients (n = 21) showed better kidney function compared to tacrolimus-minimized patients (n = 63) after conversion. However, a significant improvement in kidney function was observed in the eGFR < 60 mL/min/1.73 m2 group (n = 19) 12 months after initiation of mTOR inhibitors, for both patient groups with early+mid starters (n = 7, stating within 1 year after LT) and late starters (n = 12, starting over 1 year after LT). mTOR inhibitors were safely administered without serious adverse events that led to drug discontinuation. Conclusions: We demonstrated that patients with renal impairment showed significant improvement in renal function regardless of the timing of mTOR inhibitor start, suggesting that switch to mTOR inhibitors may be beneficial when renal function declines.